Effect of cross-linking degree of EPDM phase on the electrical properties and formation of dual networks of thermoplastic vulcanizate composites based on isotactic polypropylene (iPP)/ethylene–propylene–diene rubber (EPDM) blends. Issue 78 (9th August 2016) - Ma, Lifeng; Bao, Ruiying; Liu, Zhengying; Yang, Wei; Yang, Mingbo
Abstract : Thermoplastic vulcanizates (TPVs), as a special class of high-performance thermoplastic elastomers, have been widely used in the automotive industry, building, and electronics due to their good processability and recyclability. Abstract : Thermoplastic vulcanizates (TPVs), as a special class of high-performance thermoplastic elastomers, have been widely used in the automotive industry, building, and electronics due to their good processability and recyclability. Here, the electrical performance and the formation of dual networks of TPV composites filled with carbon black (CB) based on isotactic polypropylene/ethylene–propylene–diene rubber (iPP/EPDM) blends was investigated by varying the content of the curing agent, phenolic resin (PF). With the incorporation of 6 wt% PF, the crosslinking degree of the EPDM phase reaches a high value of 47.4 wt% and the domains reach the smallest size. The electrical percolation threshold of TPV/CB composites decreases as the cross-linking degree increases and at last maintains a steady value of 13.9 wt%. The morphological structure, dynamic rheology behaviors and crystallization behaviors of TPV/CB composites were characterized to explain the selective dispersion of CB particles and the microstructure evolution of TPV/CB composites. With an increase in the curing degree of the EPDM phase, a denser dual network including the CB conductive network and the network of EPDM particles is formed in the iPP matrix. This study provides an effective strategy to realize the control of electrical properties and the formation of dual networks of TPV composites, and can be easily introduced into industrial applications.